A correlational study on organizational culture and leadership style - Abenoja, Jemar B.; Blase, Dhamian John C.; Almagro, Ronald E. (goodwood publishing, 2025)
Purpose: This study aimed to explore the relationship between organizational culture and leadership styles among Local Government Unit (LGU) departments in the municipality of Santo Tomas, Davao del Norte. Research Methodology: Prior to data collection, the respondents were presented with a letter requesting their cooperation in completing the questionnaires. The researchers personally introduced themselves, explained the study objectives, and distributed questionnaires. After providing sufficient time for respondents to complete the questionnaires, they were collected. Results: Results revealed that the independent variable, Organizational Culture, had a mean score of 4.45, which was interpreted as